ARE PULP SENSIBILITY TESTS STILL SENSIBLE? - Farid, Huma; Khan, Farhan Raza; Pasha, Lubna; Shinwari, Muhammad Saad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Electric and thermal tests are the most commonly employed methods for the diagnosis of pulp health status. The objectives of our study are to assess the validity, yield and accuracy of cold and electric pulp tests in determining pulp vitality of teeth requiring endodontic treatment. Methods: A cross sectional study was carried out at the Dental Clinic of Aga Khan University Hospital on 75 patients requiring endodontic treatment. Before commencement of endodontic treatment, a provisional diagnosis of pulp status was made using an electric pulp tester and cold test. The tooth was then labelled as either vital or necrotic. Then an access openings was made and tooth’s actual pulp status (vital/necrotic) was determined by observing bleeding in the pulp chamber. The validity, yield and accuracy were calculated on the basis of these findings. Results: The sensitivity, specificity, positive predictive value and negative predictive value and accuracy of cold test were 84%, 88%, 93%, 73% respectively. The sensitivity & specificity of electric test were 82% and 88% respectively whereas the positive predictive value, negative predictive value and accuracy of electric test were 93% and 71% respectively. The accuracy of cold and electric pulp test were 85% and 84% respectively. Conclusion: Both cold test and EPT have similar sensitivity, specificity and accuracy values. Although vitality tests have a promising future in diagnosis of pulp health status but within limitation of this study we found that sensibility tests have satisfactory validity and accuracy values to be used routinely prior to endodontic and restorative treatments especially when used in conjunction with one each other.